2017
DOI: 10.1051/0004-6361/201730856
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the thermal infrared continuum in solar flares

Abstract: Aims. Observations of the Sun with the Atacama Large Millimeter Array have now started, and the thermal infrared will regularly be accessible from the NSF's Daniel K. Inouye Solar Telescope. Motivated by the prospect of these new data, and by recent flare observations in the mid infrared, we set out here to model and understand the source of the infrared continuum in flares, and to explore its diagnostic capability for the physical conditions in the flare atmosphere. Methods. We use the one-dimensional (1D) ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 60 publications
(100 reference statements)
1
39
1
Order By: Relevance
“…Two mid‐IR sources were observed to be cospatial with WL and hard X‐ray foot points. The flux at both wavelengths is of the same order, lending support to a thermal optically thin origin, a conclusion further reinforced by results of radiative hydrodynamic simulations by Simões et al (). Two other events were registered at 10 μm: SOL2014‐08‐01T14:47 (Miteva et al, ) and SOL2014‐10‐27T14:22 (Kaufmann et al, ), the last one classified as X2.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Two mid‐IR sources were observed to be cospatial with WL and hard X‐ray foot points. The flux at both wavelengths is of the same order, lending support to a thermal optically thin origin, a conclusion further reinforced by results of radiative hydrodynamic simulations by Simões et al (). Two other events were registered at 10 μm: SOL2014‐08‐01T14:47 (Miteva et al, ) and SOL2014‐10‐27T14:22 (Kaufmann et al, ), the last one classified as X2.…”
Section: Introductionsupporting
confidence: 68%
“…The mid‐IR flux can be explained, as in Trottet et al (), as optically thin thermal bremsstrahlung emission of a heated chromospheric plasma, since fluxes of the two events are similar. Moreover, Simões et al (), using radiative hydrodynamic simulations, have demonstrated that the mid‐IR emission from solar flares may be accounted by optically thin thermal bremsstrahlung due to the increase of the electron density in the chromosphere, as a consequence of the ionization of hydrogen under non local thermodynamical equilibrium (non‐LTE) conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Allred et al (2005) used more sophisticated chromospheric heating models and found that back-warming contributes only 10% to the heating. In a recent study, Simões et al (2017) used RADYN simulations to determine the formation of the infrared continuum in flares and found no enhancement in the photospheric blackbody emission.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these models are currently widely used (e.g., Heinzel & Avrett 2012;Trottet et al 2015;Kleint et al 2016;Simões et al 2017). When velocity or the position of the flare transition region is modified in phenomenological models, the gas density must also change and is not correctly given by hydrostatic equilibrium.…”
Section: Discussion and Applicationmentioning
confidence: 99%